(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
HIV patients require proper nutrition for health management, and nutrition education and counselling services in primary healthcare help them make informed decisions about dietary practices, promoting physical well-being and economic welfare. This study aimed to explore and describe the lived experiences of PLWHIV in accessing nutrition education and counselling. This study was conducted in Lusaka District, Zambia. It adopted a hermeneutic phenomenological design. A total of 25 participants, aged between 20 and 60 and on antiretroviral therapy (ART) for over three years, were purposively selected, and semi-structured interviews were used to collect data. The study revealed that individuals with PLWHIV benefited from nutrition education and counselling, despite challenges like transportation, limited resources, and personnel shortages. The study concluded that nutrition education and counselling significantly impact PLWHIV’s health, leading to positive changes in dietary practices and overall well-being. However, challenges in accessibility and acceptability persist, requiring improvements in healthcare infrastructure and resources. Recommendations include enhancing nutrition counselling services, promoting regular physical activity, collaborating with healthcare facilities and community organisations, monitoring and evaluating services, and identifying best practices to enhance care quality.